The Strategy to Encounter Limited Capacity of Critical Care for COVID-19 Children - Saptadi Yuliarto (Medical Faculty of Brawijaya University, Indonesia, 2022)
Coronavirus disease (COVID) â€“ 19 morbidity rates in Indonesia have exponentially increased since its first case in March 2020. To date, 15,438 (0.004%) Indonesian population have been confirmed with Covid-19. Although it is only 0.004% from all of Indonesian, the patient's enhancement is high, also, the patients who recover just only 21.3%, It would endanger the healthcare capacity in Indonesia.1 Recent data from the Indonesian Health Ministry revealed 1,065 (6.9%) confirmed COVID-19 are at young ages. Considering confirmed to suspected/ probable case ratio was 1:2.1, it is estimated that 2,236 children in Indonesia require treatment with COVID-19 protocols. According to the China dataâ€™s, the prevalence of moderate to critical illness in children was 44.5%.2Â If applied in Indonesia, to date, about 995 children need intensive care treatment, which it will rise around 10-40 patients in each day